Diagnostiska metoder för växtvirus i nematodvektorer - Andersson, Veronika; Klingberg, Helene (2007)
Tobacco Rattle Virus (TRV) is a soilborne plant virus. It is an important pathogen in potatoes where it causes spraing disease. This disease can lead to significant economical loss for the farmer, so it is imperative to get the proper diagnose before planting. TRV is spread naturally by free-living nematodes (Trichodorus and Paratrichodorus). Transference of TRV to a plant occurs when the virus-carrying nematodes feed on plant roots. The relationship between virus, nematodes and plants is complicated, and has to these days not been fully characterized. The diagnostic methods available today do not work sufficiently. The process is made even more complicated by the fact that TRV occurs naturally in a great number of different strains. This leads to problems with molecular diagnosis, since there is a risk that the virus and antibodies used do not match. Today, most diagnosis is carried out by the process of biological testing. There are, however, several problems with this method. It is for example both expensive and time-consuming. There is a need for new diagnostic methods that are fast, cheep and reliable. One such method could be negative contrasting using transmission electron microscope (TEM). Using this method, virus particles can be identified quickly as TRV is easily recognizable due to its characteristically rectangular shape. In order to correctly diagnose a specific strain of virus, the appropriate antibodies could be used. At SLU in Alnarp there is knowledge of nematodes and plant virus diagnosis, and an electron microscope available for use in this study. This study can be seen as a pilot project for the use of electron microscopy for the diagnosis of TRV.